Analisis Rantai Nilai Agroindustri Keripik Nenas di Kecamatan Tambang Kabupaten Kampar - Novia Dewi; Jum’atri Yusri (Fakultas Pertanian, Universitas Riau, 2015)
Value Chain Analysis is a valueable analytical tool to understand activities and provide information on company position in the value in the form of product and service value. The Value Chain Analysis helps the company to indentify a company position and analyze activities in value chain and to reduce or eliminate activities that are not create additional value or product and services. In the field of pineapple chip agroindustries facing with low price and low of bargaining position. Those condition make the company in a difficult situation to take decision. Quality of pineapple chips are needed to be increasing. The company can determine competitive strategy and low cost. The company must maintain and improve the relationship with customers.